Effects of angler’s groundbaits on fish physiology and growth - Dorottya Lilla Fazekas; László Antal; László Ardó; Béla Halasi-Kovács; Zsuzsanna J. Sándor; Zsolt Pirger; Flórián Tóth; Zoltán Vitál; András Specziár; Attila Mozsár (Scientific Reports)
Abstract Although angler’s groundbaits (GBs) can be an important food resource for fish, we do not know much about the effects of GB consumption on the growth and health of fish. To fill this knowledge gap, we conducted a controlled, six-week long feeding trial (feeding ration: 2% of body weight) with common carp at 22 °C (Cyprinus carpio, mean initial body weight: 557 g) to test the effect of two GBs composed mostly of animal-derived ingredients (AN-GBs) and two plant-based GBs (PL-GBs) relative to one aquaculture feed, as a control (five treatment altogether). Consumption of PL-GBs resulted in lower growth rate than AN-GBs, presumably due to the low protein content. However, the unit biomass increment per unit nitrogen input was higher in PL-GBs. Although PL-GBs resulted in reduction of hepatic energy reserves, hepatosomatic index, viscerosomatic index, and body condition did not differ among the treatments. We did not find differences in expression of inflammatory cytokines in the liver. In conclusion, AN-GBs more effectively increases the carrying capacity of fisheries, but fish sequester a higher portion of nitrogen content of PL-GBs –PL-GB input can be more effectively counterbalanced by fish removal. Finally, the GB consumption does not pose a health risk to fish.